HAYDAR XORAZMIYNING "MAHZAN UL-ASROR" DOSTONI LINGVISTIK XUSUSIYATLARI - Ne'matova O'g'iloy Akram qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
This article examines the linguistic features of Haydar Khorezmi's poem "Makhzan ul Asror" (The Treasury of Secrets). The lexical, grammatical, and stylistic aspects of the work are analyzed and compared with Nizami Ganjavi's poem of the same name. The research reveals Haydar Khorezmi's unique language and style characteristics, as well as the peculiarities of the literary language of the period in which the work was created.